ANALISIS PERMUKAAN NANOPARTIKEL FERIT SENG BERDASARKAN ADSORPSI ISOTERM GAS NITROGEN - Kadarisman, Kadarisman; Nurhasanah, Iis (BERKALA FISIKA, 2020)
This research aims to analyze surface characteristic of zinc ferrite nanoparticles based on the N2 adsorption isotherm. The morphology and size of zinc ferrite nanoparticles were observed using a scanning electron microscope. Analysis of N2 adsorption isotherm using the Brunauer- Emmett-Teller equation obtained a specific surface area of 9.78 m2/g and mesoporous structure. Zinc ferrite nanoparticles were composed of spherical primary particles with a diameter of 67 nm. The size of the nanoparticles obtained from the specific surface area analysis was greater than the scanning electron microscope image analysis. This finding shows that zinc ferrite nanoparticles are agglomerating to form larger secondary particles.Keywords: Zinc ferrite, nanoparticle, surface area, agglomeration